1988
DOI: 10.1159/000124983
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Sheep Adrenal Cortex: An Immunohistochemical Study with Rat Corticotrophin-Releasing Factor Antiserum

Abstract: Using indirect immunohistochemistry and an antiserum raised against rat corticotrophin-releasing factor (CRF) we have outlined an asymmetric network of cells and varicose fibers in sheep adrenal cortex. This network was not associated with the larger splanchnic nerves, but was occasionally found in small bundles or with blood vessels; in most instances fibers were found weaving independently through cortical parenchyma. A plexus of fibers was found in the zona reticularis, with a few fibers ramifying into adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Immuno-localisation studies on CRH within the adrenal gland have demonstrated the presence of CRH within the medulla, predominantly located in cells within close proximity to the peripheral radicles of the central vein (Andreis et al, 1992;Bruhn et al, 1987;Edwards and Jones, 1988;Hashimoto et al, 1984;Vinson and Hinson, 1992). Rundle et al (1988) reported that CRH was located in an asymmetric network of cells and varicose fibres in the adrenal cortex, a plexus of fibres being located in the zona reticularis with fibres ramifying into the adjacent medulla. While CRH cells were found throughout the cortex, the greatest frequency was at the corticomedullary junction.…”
Section: Factors Regulating Venous Outflowmentioning
confidence: 99%
“…Immuno-localisation studies on CRH within the adrenal gland have demonstrated the presence of CRH within the medulla, predominantly located in cells within close proximity to the peripheral radicles of the central vein (Andreis et al, 1992;Bruhn et al, 1987;Edwards and Jones, 1988;Hashimoto et al, 1984;Vinson and Hinson, 1992). Rundle et al (1988) reported that CRH was located in an asymmetric network of cells and varicose fibres in the adrenal cortex, a plexus of fibres being located in the zona reticularis with fibres ramifying into the adjacent medulla. While CRH cells were found throughout the cortex, the greatest frequency was at the corticomedullary junction.…”
Section: Factors Regulating Venous Outflowmentioning
confidence: 99%
“…There is experimental evidence in support of the contention that glucocorticoids interact with ACTH receptors on adrenocortical cells (39). Conceivably, they may also interact with SCN messages through negative feedback regulation of an intraglandular mini-HPA axis (21,40,46). In support of the latter possibility, it has been shown that modulation of the adrenocortical sensitivity to ACTH stimulation is a major effect of intraadrenal corticotropin-releasing hormone (CRH) (45) and that the adrenal content of CRH is significantly reduced by cortisol treatment in rats (1).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, a tissue CRF similar to hypothalamic CRF has been demonstrated in the mammalian adrenal medulla (Hashimoto et al 1984;Bruhn et al 1987;Nicholson et al 1987;Edward and Jones 1988;Minamino et al 1988), and a report by Rundle et al (1988) demonstrated that a CRF-like substance is also present in the sheep adrenal cortex. In addition, a CRF identical to hypothalamic CRF has been isolated from another steroid-producing organ, the ovine testis (Audhya et al 1989).…”
Section: Introductionmentioning
confidence: 96%